Market Fragility and Stock Returns: Evidence from Tehran Stock Exchange - Javad Sadeghi Panah; Mansour Garkaz; Parviz Saeidi; Alireza Matoufi (Iranian Journal of Accounting, Auditing & Finance)
Recognising and investigating stock return behaviour has always been one of the most critical issues in scientific and investment communities. In recent years, factor models have been used in many studies related to stock return prediction. This research is based on a six-factor model, including the Fama-French five-factor model plus the market fragility factor. The explanatory power of this model has been examined in the Tehran securities market from 2009 to 2018 for 117 companies. The results show that the explanatory power of the six-factor model is better than the Fama-French five-factor model in the Iranian capital market. The results also suggest that market fragility has a significant negative relationship with stock returns. Policymakers can consider this result in financial and investment issues and people interested in this issue.